Centrifugal Concentration of Mandailing Natal North Sumatera Gold Ores Using Knelson Concentrator - Oediyani, Soesaptri; Triana, Tiara; Ifzan, Ifzan; Mamby, Hasudungan Eric (World Chemical Engineering Journal, 2021)
Gravity concentration is the type of separation process of minerals based upon the difference in density. This technique has been known for centuries. It has the ability to separate the valuable minerals with relatively low production cost and little environmental impact, such as gold ores. Separation of gold from gangue minerals by using gravity concentration has been used for decades. In fact, it has the limitation to process fine particles. In attempt to recover fine particles using gravity concentration methods, the technique has been developed by combining centrifugal force. One of wellknown devices, Knelson Concentrator, was used to separate gravity recoverable golds (GRG) from the gangue minerals of Mandailing Natal (North Sumatera) sulfide complex gold ores with -200# of particle size. The head grade of ores was 5 g/t of gold. The ores were separated by using Knelson Concentrator with variation of pulp density, feeding rate, and water fluidization pressure. The results have proved that these three variables have particular impacts on gold recovery. The recovery of gold was increased by the increasing of pulp density until it reached the optimum level in 25% of solid with 86.9% of gold recovered, and then decresed by increasing of pulp density into 84.88% of gold with 30% of solid in pulp. It has the same trends in variation of feeding rate and water fluidization pressure. The highest point with 87.08% of recovery and 17.88 g/t of concentrate grade was anchieved at 25% of solid, 0.7 kg/minutes of feeding rate, and 2.7 kg/cm2 of water fluidization pressure.